Macrogenomics reveal the effects of inter-cropping perilla on kiwifruit: impact on inter-root soil microbiota and gene expression of carbon, nitrogen, and phosphorus cycles in kiwifruit - Gao, Ning; Wen, He; Shang, Zhiwei; Zou, Yifei; Zhao, Wei; He, Yun; Yang, Sen; Zhang, Heng; Qin, Jiahao; Zhu, Sixi; Wang, Wenhua (Frontiers in Microbiology, 2024)
Intercropping systems can improve soil fertility and health, however, soil microbial communities and functional genes related to carbon, nitrogen and phosphorus cycling under the intercropping system of mesquite and perilla have not been studied. Therefore, in the present study, different planting densities and varieties of Perilla frutescens (L.) Britt and kiwifruit were used for intercropping, and changes in soil microbial communities and carbon, nitrogen, and phosphorus cycling genes in kiwifruit inter-roots under inter-cropping conditions were investigated by macro-genome sequencing technology. The results showed that intercropping with Perill caused a decrease in most soil nutrients, soil enzyme activities, and had a significant impact on the microbial (bacteria and fungi) diversity. Inter-cropping increased the relative abundance of the dominant bacterial phylum “Proteobacteria” and “Actinobacteria” by 47% and 57%, respectively, but decreased the relative abundance of the dominant fungal phylum “Chordata” and “Streptophyta” by 11% and 20%, respectively, in the inter-root soil of kiwifruit, and had a significant impact on the microbial (bacteria and fungi) diversity. In addition, inter-cropping could greatly increase the inter-root soil carbon sequestration (PccA, korA/B/C/D, fhs, and rbcl/s), carbon degradation (abfD), organic nitrogen mineralization (GDH2), denitrification (napA/B, nirB, norB), organic phosphorus mineralization (phop, phn), and inorganic phosphorus solubilization (gcd, ppk) gene abundance. The gene co-occurrence network indicated that soil korB, nirB, and gnd key functional genes for carbon, nitrogen, and phosphorus cycling in kiwifruit inter-root soils and their expression was up-regulated in the inter-cropping group. Structural equation (SEM) further showed that soil total nitrogen, organic matter, total carbon and acid phosphatase had significant effects on microbial diversity (P < 0.05) and soil carbon cycling gene korB and phosphorus cycling gene purH (P < 0.001), while korB and purH had positive effects on kiwifruit quality. In conclusion, intercropping perilla in kiwifruit orchards changed the structure of bacterial and fungal communities in the inter-root soil of kiwifruit, but I believe that intercropping perilla stimulates carbon degradation, leading to carbon emission and serious loss of soil nutrients, and that prolonged intercropping may adversely affect the quality of kiwifruit, and thus its limitations should be noted in future studies.